SOCIAL POLICY AND DISABILITY: SPECIAL EDUCATION - TAYLOR, STEVEN; Walker, Pam (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course has four purposes: 1.To help you understand how social policy affects human services and the lives of people with disabilities. 2.To give you an appreciation of the complexity of social change and social policy. 3.To provide you with an understanding of the social, economic, historical, political, cultural, and legal forces that shape policy and practices in the field of disabilities. 4.To expose you to current issues, controversies, and trends in the field of disabilities.